Appropriate age to deliver school-based sex education - earlier or later? - Kamrani, Mahnaz Akbari; Syed Yahya, Sharifah Zainiyah; Hamzah, Azimi; Ahmad, Zaiton (Malaysian Public Health Specialist Association, 2011)
Aim: To explore the perspectives of Science teachers regarding appropriate age to deliver school-based sexual and reproductive health (SRH) education in secondary schools in the Klang-Valley, Malaysia. Method: A qualitative study using in-depth interview technique was conducted among science teachers in secondary schools in the Klang Valley.